Propiedades psicométricas de la aversion to risk taking scale en una muestra de motociclistas colombianos (2021)
Every year hundreds of motorcyclists die in traffic accidents. One of the causes is the low perception of risk when driving, which influences the appearance of risky behaviors. The objective was to adapt and validate the Aversion to Risk Taking Scale (ARTS) in a sample of Colombian motorcyclists, to evaluate the perceived risk of different behaviors considered dangerous on the road. 436 motorcyclists from Nariño (Colombia) participated, with ages between 18 and 71 years (M = 28.27; SD = 8.68). The scale was updated with two new items (consumption of psychoactive substances and helmet use); A linguistic adjustment was performed, internal consistency, evidence of content validity, construct validity (exploratory and confirmatory factor analysis) and validity compared with the Self-efficacy Scale for driving were assessed. The ARTS presented optimal psychometric properties for a unifactorial structure. Optimal internal consistency values are recognized (α = .94; ɷ = .95). An inverse correlation with the Driving Self-Efficacy Scale was evidenced, corroborating the construct. The results suggest that the ARTS, adapted and updated for Colombia, is one with proven psychometric quality; therefore it is valid and reliable to evaluate the perception of risk in Colombian motorcyclists.